2021
DOI: 10.1038/s41598-021-97382-5
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure and markers of genetic damage, systemic inflammation and lung function: a Danish cross-sectional study among air force personnel

Abstract: Air force ground crew personnel are potentially exposed to fuels and lubricants, as raw materials, vapours and combustion exhaust emissions, during operation and maintenance of aircrafts. This study investigated exposure levels and biomarkers of effects for employees at a Danish air force military base. We enrolled self-reported healthy and non-smoking employees (n = 79) and grouped them by exposure based on job function, considered to be potentially exposed (aircraft engineers, crew chiefs, fuel operators and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Both of the metabolites of TDCIPP and TCIPP have fairly high ICCs ( Bastiaensen et al, 2021 ) compared to other metabolites of similar half-lives but much lower ICCs (DPHP included), providing an explanation why correlations between wristband OPEs and their metabolites have been observed more frequently than those with phthalates and PAHs. While one study reported weak correlations between PAHs in wristbands and spot urine samples in air force workers ( Andersen et al, 2021 ), another reported statistically significant correlations between six PAHs detected in the wristband and urinary metabolites in pregnant women ( Dixon et al, 2018 ). Similarly, positive and statistically significant, but relatively low to moderate, relationships were observed among children to environmental phenols (specifically BPA, triclosan, and three parabens) and 4 phthalates and phthalate replacements ( Hammel et al, 2020 ; Levasseur et al, 2021 ).…”
Section: Comparison To Other Exposure Assessment Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of the metabolites of TDCIPP and TCIPP have fairly high ICCs ( Bastiaensen et al, 2021 ) compared to other metabolites of similar half-lives but much lower ICCs (DPHP included), providing an explanation why correlations between wristband OPEs and their metabolites have been observed more frequently than those with phthalates and PAHs. While one study reported weak correlations between PAHs in wristbands and spot urine samples in air force workers ( Andersen et al, 2021 ), another reported statistically significant correlations between six PAHs detected in the wristband and urinary metabolites in pregnant women ( Dixon et al, 2018 ). Similarly, positive and statistically significant, but relatively low to moderate, relationships were observed among children to environmental phenols (specifically BPA, triclosan, and three parabens) and 4 phthalates and phthalate replacements ( Hammel et al, 2020 ; Levasseur et al, 2021 ).…”
Section: Comparison To Other Exposure Assessment Toolsmentioning
confidence: 99%
“…Alternative configurations that have not been directly compared to the standard sampler (i.e., a wristband worn on a wrist) include wristbands worn as air samplers on participants with no dermal contact aside from brooches/lapels ( Aerts et al, 2018 ; Bullock et al, 2020 ; Mendoza-Sanchez et al, 2021 ; Swanson et al, 2018 ; Andersen et al, 2021 ), silicone military-style dog tags worn around the neck ( Poutasse et al, 2022 ; Poutasse et al, 2020 ), and pet tags ( Wise et al, 2020 ; Wise et al, 2021 ; Poutasse et al, 2019 ). Two studies have utilized PDMS tubing to create silicone wristbands and anklets, but these studies were not concerned with environmental chemical exposure ( Roodt et al, 2018 ; Wooding et al, 2020 ).…”
Section: Comparison To Other Exposure Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MN assay in transferrin-positive peripheral blood RET was performed according to the method that was developed by Abramsson-Zetterberg et al [35] as previously described [39]. Briefly, the whole blood samples were processed within 7 days after collection and transferrin-positive (+CD71) RET were isolated by immunomagnetic separation according to the instructions of the CELLection™ Pan Mouse IgG Kit (Invitrogen, Thermo Fisher Scientific, Waltham, MA, USA), using a FITC Mouse Anti-human CD71 antibody (BD Biosciences, San Jose, CA, USA).…”
Section: Micronucleus (Mn) Assay In Reticulocytes (Ret)mentioning
confidence: 99%
“…It is a sensitive high-throughput method with high potential in biomonitoring studies [35]. The method has been previously used for studying the potential genotoxicity of pesticides [36], disinfection by-products [37], industrial pollution [38], and polycyclic aromatic hydrocarbons (PAHs) [39]. As application of flow cytometry allows for the rapid analysis of large amounts of cells, the method also has benefits compared to microscopically analyzed endpoints which suffer from the limited number of reasonably countable cells and potential individual differences in analyzing cells [40].…”
Section: Introductionmentioning
confidence: 99%